Labile organic carbon dynamics in continental shelf sediments after the recent collapse of the Larsen ice shelves off the eastern Antarctic Peninsula: A radiochemical approach - Isla, E.; DeMaster, D.J. (Geochimica et Cosmochimica Acta, 2018)
Labile organic carbon (LOC) dynamics (i.e., of recently produced, planktonic material) and sediment dynamics were studied in the seabed using naturally occurring C-14(org), and Pb-210 measurements in the region where the Larsen Ice Shelves A and B were floating almost two decades ago. A non-steady-state diagenetic model was used to estimate sediment mixing coefficients as well as LOC fluxes to the seabed and LOC turnover times (i.e., mean residence times) in a suite of 14 sediment cores from the continental shelf, including a glacial trough. At four of the stations, cores were collected during 2007 and 2011 cruises, enabling a time-series approach for understanding the evolution of sedimentary processes and LOC dynamics in the deposits below a collapsed ice shelf. Sediment mixing coefficients, based on non-steady-state Pb-210 profiles, varied between 0.01 cm(2) y(-1) and 1.6 cm(2) y(-1) in these post-ice shelf sediments. These values were similar to those found in polar deep-sea environments, where sedimentary conditions are less dynamic than in shallower provinces. LOC, whose abundance decreased uniformly with depth, was detected to depths ranging from 2 to 16 cm, with LOC seabed inventories varying from 1.5 to 22 mg LOC cm(-2). Excess Pb-210 and LOC fluxes were relatively uniform across the study area suggesting that similar particle fluxes have taken place within theLarsen system since the disintegration of the various ice shelves. The LOC mean residence time at the different stations varied from 3 y to >60 y. The C-14(org), approach, calculating LOC content based on a two-end member model with planktonic 14C(org) as the labile carbon end member, most closely correlated with the lipid content of the sediment, which has been considered one of the best descriptors of reactive organic matter readily available to benthic consumers. We suggest that the irregular combination of sea ice coverage, organic matter production and supply to the sea floor introduce scatter in the determination of sediment and LOC dynamics such that short-term temporal (<5 years) and spatial trends could not be readily resolved.

Determining rates of sediment accumulation on the Mekong shelf: Timescales, steady-state assumptions, and radiochemical tracers - DeMaster, D.J.; Liu, J.P.; Eidam, E.; Nittrouer, C.A.; Nguyen, T.T. (Continental Shelf Research, 2017)
Thirty-two kasten cores, collected from the proximal Mekong continental shelf, have been analyzed for their excess 210Pb distributions in an effort to establish rates of sediment accumulation over the past 100 years. The length of the cores varied from 0.5 to 3 m, and stations sampled topset, foreset, and bottomset beds (water depths 7–21 m). Apparent excess 210Pb sediment accumulation rates ranged from > 10 cm/y (no down-core decrease of excess activity over 300 cm core length) near the Song Hau river mouth, to 1–3 cm/y in topset and foreset beds within 20–50 km of the river mouth, to rates as low as 0.4 cm/y in cores from bottomset beds. The 210Pb sediment accumulation rates yield an overall sediment burial rate of 6.1 × 1013 g/y for the proximal deltaic deposits, which corresponds to 43% of the total modern Mekong sediment burial on the southern Vietnam shelf (1.4 × 1014 g/y; based on our 210Pb and seismic data and 210Pb data from the literature). This shelf burial rate is in reasonable agreement with current long-term estimates of Mekong River sediment discharge (1.3–1.6 × 1014 g/y) from the literature. The inventory of excess 210Pb in the proximal Mekong deltaic deposits indicates that the shoreward flow of offshore water (entrained during river/ocean mixing) is approximately twice the flow of the Mekong freshwater discharge. Organic-carbon 14C ages were measured on 10 cores from the proximal Mekong delta and compared to 210Pb sediment accumulation rates in the same core. The 210Pb accumulation rates in all 10 cores were considered to be more robust and accurate than the 14C geochronologies, primarily because of down-core variations in the source of organic carbon deposited on the seafloor (old terrestrial carbon versus younger marine carbon). Variations in the source of organic carbon accumulating in the seabed were resolved by measuring the δ13C value of the seabed organic carbon.
Keywords: 14C geochronology; 210Pb geochronology; Deltaic sediment accumulation rates; Mekong delta; Mekong sediment budget